Check This Word Out! Exploring the Factors That Affect Students’ Vocabulary Learning Using Smartphones via Partial Least Squares - Alhabahba, Mohammad Madallh; Ali Mahfoodh, Omer Hassan; Pandian, Ambigapathy; Mohammad, Yazan Mdala; Ahmed, Enas Waleed; Albdour, Ali; Al Bazar, Hussein (Hindawi Publishing Corporation, 2014)
A rigorous understanding of the use of Smartphones for foreign language vocabulary acquisition is crucial. Employing the technology acceptancemodel, this study aims to investigate students’ behavioural factors affecting Saudi students’ attitudes towards employing Smartphones for foreign vocabulary acquisition. Two hundred and seventy-three students studying in a preparatory year programme were surveyed. SmartPLS was employed to analyse the data obtained fromthe study’s sample. The results revealed that perceived usefulness and attitude proved to be significantly and positively related to vocabulary development. In addition, perceived usefulness and perceived ease of use proved to be significant predictors of students’ attitudes towards the use of Smartphone for vocabulary learning.However, the study showed that the relationship between perceived ease of use and vocabulary development is not significant.Thus, publishers of dictionariesmay find it necessary to take into account the important role played by the design of dictionaries interfaces in facilitating the use of dictionaries in Smartphones. Furthermore, teachers and educators are encouraged to employ creative activities (e.g., word guessing games) that invest students’ use of Smartphones to learn vocabularies. Using Smartphones in learning improves interaction among students and teachers. Discussion and conclusions are also provided.